Strikingly different selling : 6 vital skills to stand out and sell more - Merrill, Dale; Savage, Scott; Illig, Randy; Colosimo, Jennifer (Ascent Audio, 2022)
You are competing with the top salespeople in your industry for the same customers. For each sales opportunity there is only one winner. What separates a "winner" from the rest of the very best and makes them "strikingly different"? Six years of focused research involving more than 2,800 sales professionals from 135 countries reveals the six vital skills that separate top sales performers from the herd. What really works to stand out and sell more? In their book Strikingly Different Selling, Dale Merrill, Scott Savage, Jennifer Colosimo, and Randy Illig reveal the secrets to consistent, predictable sales success. The author team found that most consultants and sales professionals believed they were doing a great job in their client interactions. Yet 70 percent of the time client executives felt their meetings with sales professionals were a waste of time. To the authors, this was a major surprise. But, for the "Strikingly Different" sales professionals, there were six things they did to consistently outperform their competitors and radically change their client interactions and results. Listen to Strikingly Different Selling and learn the details behind the six skills.